MODEL PENERIMAAN MAHASISWA BARU JURUSAN PENDIDIKAN BAHASA INGGRIS IKIP PGRI SEMARANG - Siti Lestari; Ajeng Setyorini; Entika Fani Prastikawati (Universitas PGRI Semarang, 2011)
The goals of this research are: (1) to find out the requirements to be the Englishtecher candidate, (2) to find out if motivation is one of the factors which needs to beconsideres in students; recruitement system, (3) to fdesign the model of students?óÔé¼Ôäórecruitment system in English department of IKIP PGRI Semarang. The instrumets ofthis study are quetionaires which were distributed to the samples. The samples are thestduents of english department which was randomy selected and six English teachers ofsenior high school in Semarang. Those schools were: 1 state senior high school, 1private high school, 2 state vocational schools and 2 provate vaocational schools. Thetresearch was conducted for 1,5 month. The result of this study shows that the users(schools) have less content over the English department graduates?óÔé¼Ôäó competence. Thoseare profesionalism, pedagogic, social and performance. The graduates are consideredto have low pedagogic competence(33.3%) and less in performance (16.7%). Theresult of the analysis on questionaires filled by the students revealed that the highermotivation of the students, the higher their achievement. The result of the study willlead to the designing of model which include motivation as one of the factors inrecruiting new students of English Deparment. The users dicontent is worth consideredas the supporting factors in improvement. The improvement can be started from thestudents recruitment.Key words: motivation, result of the study, profesionalism, and students RecruitmentModel